EFFECT OF FERMENTED MANURES ON INTERCROPPED SUDAN GRASS (SORGHUM SUDANESE L.) AND CLITORIA (CLITORIA TERNATE) GROWN IN AN ARID SALINE ENVIRONMENT - Awad O. Abusuwar (Journal of Animal and Plant Sciences, 2019)
A field experiment was conducted at Hada Al-Sham Research Station of King Abdulaziz University over two successive seasons (2015/17) to evaluate the effect of a cereal (Sudan grass) intercropped with a leguminous (Clitoria) forage under saline arid environment. The treatments, besides intercropping, included fermented poultry and cow manures applied separately and in combination. A split plot design with three replicates was used. Intercropping treatments were randomly assigned to main plots whereas the manure treatments were assigned to sub- plots. Results showed  significant differences  for both fermented poultry and cow manures when combined together compared to other treatments for both growth and yield parameters. Moreover, intercropping of Clitoria with Sudan grass significantly increased both fresh and dry forage yields compared to sole crop during both seasons. The increments in dry forage resulting from combined poultry and cow manures ranged from 53.7 to 118% in the first season and from 146 to 514% in the second season. On the other hand, the increments in dry forage resulting from intercropping ranged from 82.4 to 203% in the first season and from 58.7 to 237% in the second season. It can be concluded that fermented organic poultry and cow manures with intercropping of grasses and legumes can boost forage productivity under arid saline environment.
Keywords: Arid saline soils; Forage productivity; Grass-legume mixture; Organic manures